Magnetic drum separator for removal of ferromagnetic impurities from sugar - Kuyevda, Valery; Danyluk, Valery; Kuievda, Yulia (My University, 2013)
This separator has specific pole geometry for creating high gradient of magnetic field and itsconcentration on the working area surface for providing sufficient forces of removing even low magnetic contaminants from the sugar flux. The rotation of the drum creates the conditions for guaranteed removal offerromagnetic impurities in the discharge zone, where the magnetic field is absent. Separation qualitycomplies with current standards.
Keywords: magnetic drum separator; ferromagnetic contaminants in sugar; магнітний барабанний сепаратор; феромагнітні домішки у цукрі; магнитный барабанный сепаратор; ферромагнитные примеси в сахаре; кафедра електропостачання і енергоменеджменту